PERLINDUNGAN HUKUM PEMEGANG POLIS ASURANSI DALAM MEMBAYAR KLAIM ASURANSI - Anisa, Darania; Ariyanti, Ovi; Asari, Aang; Hidayat, Ma’ruf (Syekh Ali Hasan Ahmad Addary State Islamic University, 2023)
Increasing public awareness and trust in the insurance sector is considered capable of providing protection from various uncertainties during a pandemic. If you look at the performance of the insurance industry, in the third quarter of 2021 the total income for the life insurance industry in Indonesia will reach Rp. 171.4 trillion or a significant growth of 38.7 percent from the 2017 period. However, total claims have decreased from year to year, in 2019 it reached 114 trillion and in 2021 it reached Rp 107 trillion, down 2 percent. So that there are complaints from the public regarding the difficulty of submitting an insurance claim, rejection of claims from insurance companies even though they always pay insurance premiums, of course, this is an important note to resolve. Legal protection is found for the policy holder/insured in the payment of insurance claims, namely if the default insurer does not perform the performance as agreed in the insurance policy, the insured can take legal action in the form of a lawsuit through the court or settlement through the existing mechanism in the insurance policy. And also the obligation of the insurer to the insured is to pay insurance claims in accordance with the amount of coverage stated in the insurance policy.